Pengaruh Karakteristik Individu, Disiplin Kerja dan Kepuasan Kerja Terhadap Etos Kerja Pegawai Pada Badan Pusat Statistik di Kabupaten Alor - Hermayanti Hermayanti; Theresia Lounggina Luisa Peny; Alvonso Fanisius Gorang; Mesak Yamres Awang (Peneliti.net, 2022)
This study aims to determine the effect of individual characteristics, work discipline, and job satisfaction on work ethic. The analytical method used is a multiple linear regression analysis technique with t-test and simultaneous test or F-test results of the research partially and simultaneously obtained a significance value of individual characteristic variables of 0.026, work discipline of 0.005, job satisfaction of 0.007, and simultaneously a significance value the result of the F test is 0.000, testing the hypothesis proposed in this study is as follows: There is an influence of Individual Characteristics on work ethic, work discipline on work ethic and Job Satisfaction on Work Ethics of employees of the Central Bureau of Statistics of Alor Regency.